INTERTEXTUAL STUDY “WHEN YOU WERE MINE BY REBECCA SERLE AND ROMEO & JULIET BY WILLIAM SHAKESPEARE” - Annisa Annisa; Harianto II Harianto II (PHILOLOGY Journal of English Language and Literature, 2021)
This paper entitled Intertextual Study “When Were Mine by Rebecca Serle and Romeo & Juliet by William Shakespeare”. The research method is a qualitative descriptive method with an intertextual approach. The problem discussed in this article is how the intertextual relationship between "When Were Mine by Rebecca Serle and Romeo & Juliet by William Shakespeare". The scope of the problem discussed is the intrinsic elements and stories of novels and drama scripts whose intertextual relationships are reviewed from the theme and plot. Also describes the intrinsic elements and intertextual relationships “When Were Mine by Rebecca Serle and Romeo & Juliet by William Shakespeare” in terms of themes and plot. Based on the results of the discussion, the intertextual relationship between “When Were Mine by Rebecca Serle and Romeo & Juliet by William Shakespeare” is the similarity of theme and plot. In addition, there are differences between the two novels and the drama. The similarity between the two stories is that both novels have the theme of romance, containing teachings about human life to be able to behave and act according to logic.